Parâmetros de qualidade do queijo colonial: percepção do consumidor & relação de consumo - Arbello, Deisi Dariane Rodrigues (2021)
Cheese is a product that has a high nutritional value and is widely produced in southern Brazil. Colonial Cheese is a type of cheese made mainly in family farms in an artisanal way so as to add value to its raw material. Colonial cheese does not have technical regulations on identity and quality, so it can be produced using different techniques by producers, making it difficult to standardize. The consumption of milk and dairy products can be affected by some factors, including lactose intolerance. Some dairy products have low levels of lactose, such is the case of aged cheeses and Colonial Cheese. Therefore, this study aimed to verify the quality parameters, the consumer perception and the factors that interfere with the consumption of Colonial Cheese. The consumer profile and quality parameters of Colonial Cheese marketed in the Rio Grande do Sul "Campanha" region were analyzed, and the quantification of lactose levels, dairy consumption ratio and lactose intolerance were performed. With the results obtained, it can be inferred that the physical-chemical parameters of the Colonial Cheeses analyzed showed a significant difference (p <0.05), showing variation between the products. Regarding the lactose content, in 75% of the analyzed products the carbohydrate was not detected, and the other 25% of the samples were classified as lowlactose cheese. Regarding the perception of Colonial Cheese consumers, it was observed that consumption is not only linked to sensory attributes, but also to health issues, such as quality and proven origin. Regarding the consumption of dairy products and lactose intolerance, it was observed in the survey that the majority of consumers who claim to be intolerant do not exclude dairy products from their diet, contradicting, in this way, some studies, hypotheses and guidances for the exclusion of products by this specific group of intolerants.